Degradation kinetics of the physicochemical and phytochemical properties of MD2 pineapple juice during heat treatment and storage - Siti Mariam A Rani; Khairul Farihan Kasim; Lee, Boon-Beng; Nor Hidawati Elias; Mohd Khairul Ya’kub; Noor-Soffalina Sofian-Seng (Penerbit Universiti Kebangsaan Malaysia, 2025)
Thermal processing is crucial for preserving fruit juice while minimising nutritional loss. A comprehensive study of heat treatment and storage effects on a popular pineapple hybrid, MD2, is required to enhance juice marketability. This study examined the thermal degradation kinetics of MD2 pineapple juice on the physicochemical and phytochemical properties by heat treatment at different temperatures (40-90 °C for up to 150 min), and storage conditions (-20, 1, 4, 7 and 27 °C). Physicochemical properties were determined based on the total soluble solids (TSS) content and browning index (BI). Meanwhile, phytochemical properties were evaluated on the pineapple juices’ vitamin C and protein contents. Results showed that TSS and BI remained constant, while vitamin C and protein contents declined during the heat treatment. Pineapple juices’ thermal degradation followed first-order kinetics, with vitamin C degrading faster at higher rate constants (4.38 × 10³/min during heat treatment and 6.23 × 10³/min during storage) as compared to protein content (4.30 × 10³/ min and 5.38 × 10³/min, respectively). These findings may provide information for food manufacturers in optimising temperature and time for preservation and safety of pineapple juice.